Evaluation the serum levels of some non-enzymatic antioxidant factors among diabetic patients with and without nephropathy - Obeid, Shahad F. (Edelweiss Applied Science and Technology, 2024)
Hyperglycemia, an elevated concentration of blood glucose, is the characterization of diabetes mellitus caused by insufficiencies in insulin synthesis or insulin action. The global health threat posed by the diabetes mellitus epidemic and its sequelae is significant According to the International Diabetes Federation (IDF), 415 million persons (ranging from 20 to 79 years old) were diagnosed with diabetes in 2015. mellitus worldwide, or 1 in 11 adults. Objective was to examine the changes in blood levels of glutathione, melatonin, and homocysteine in patients with nephropathy from diabetes, those without nephropathy from diabetes, add to controls. One hundred thirty-five participants were split into three categories for the study, The initial cohort consists of forty-five individuals diagnosed with diabetes nephropathy. 45 individuals with diabetes who do not have nephropathy make up the second group. From December 2023 until the end of March 2024, 45 healthy individuals served as controls in the third group. A venous blood sample of five milliliters was obtained from the case and control groups. Centrifugation was used for 10 minutes at 2000 rpm to separate the serum from the blood samples, which were transported to the laboratory under standard circumstances. Serum results were frozen at -80°C before glutathione, homocysteine, and melatonin were evaluated using colorimetric and enzyme-linked immunosorbent assays, respectively. The present study enrolled 135 participants (45 diabetic patients with diabetes nephropathy 45 healthy controls and 45 diabetic patients without nephropathy (participated in this study. According to the current investigation, the mean serum homocysteine levels of the healthy control group were higher than those of the type II diabetic (T2DM) patients with nephropathy. Also show the mean levels of serum Glutathione levels were significantly lower in T2DM with nephropathy compare to healthy control and T2DM without nephropathy. Our results demonstrated that decreased serum levels of melatonin and glutathione levels are associated with nephropathy in T2DM.